Factors Related Readiness Elementary Child Facing First Menstruation - Velga Yazia; Delvi Hamdayani (Jurnal Ilmu Keperawatan Jiwa, 2021)
The lack of understanding of adolescents about reproductive problems, even with regard to the experience of menstruation, the survey showed that most (>75%) expressed shock during menstruation, 38.4% lacked knowledge about menarche, 31.5% did not receive support from family, 45 ,2% have a bad attitude and do not accept and try to deny in the face of menarche. The purpose of this study was to determine the factors related to the readiness of elementary school children in facing the first menstruation (menarche) at SDN 11 Bancah, South Solok Regency. Research This research is an analytic survey with a cross sectional design that has been conducted at SDN 11 Bancah on July 6-7 2020. The sample of class V and VI students who have not experienced menarche is 45 respondents, the sampling technique is total sampling. The data was collected using a questionnaire. The data was analyzed using univariate and bivariate analysis with the chi-square test. The results showed that (48.9%) students who were not ready to face menarche, students who had low knowledge (55.6%), students who had bad attitudes (53.3%), students who had good family support not good as much as (53.3 %), there is a relationship between knowledge and children's readiness to face menarche, there is a relationship between attitude and readiness for children to face menarche, there is a relationship between family support and children's readiness to face the first menstruation. there is a relationship between knowledge, attitude and family support with children's readiness to face the first menstruation.